PENGEMBANGAN MEDIA RODA PUTAR PENJUMLAHAN BERBASIS STEM UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS 2 SD INPRES FATUKOA KOTA KUPANG - Timotius Lake; Chintia Marini Putri Ati; Kristina E. Noya Nahak (STKIP Subang, 2026)
This research is motivated by the low mathematics learning outcomes of grade II students of SD Inpres Fatukoa Kupang City in summation materials. The learning process that is still conventional and the use of learning media that does not actively involve students causes active students to be easily bored, lack focus, and lack enthusiasm in learning. This study aims to determine the feasibility, practicality, and effectiveness of STEM-based addition rotary wheel media in improving student learning outcomes. The research method used is Research and Development (R&D) with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The subject of the study is a second grade student of SD Inpres Fatukoa, Kupang City. Data collection techniques are carried out through validation questionnaires for material experts, media experts, and linguists, teacher and student response questionnaires, and learning outcome tests in the form of pretests and posttests. Data analysis uses quantitative descriptive analysis. The results of the study show that the STEM-based summation rotary wheel media is declared feasible based on the validation of experts, practical based on positive responses from teachers and students, and effective in improving student learning outcomes as seen from increasing pretest and posttest scores. The use of this media is able to create more interactive, interesting, and motivating learning for students in understanding the concept of quantities. Thus, STEM-based summation rotary wheel media is suitable for use as a mathematics learning medium in elementary schools.